Planting Bamboo Palms to Reduce Air Pollution and Maintain Lung Health in the Assalafi Al Fithrah Sub-district, Surabaya - Danny Irawana; Evi Sylvia Awwalia; Ratna Yunita Sari; Akbar Reza Muhammad; Rifky Dwi Aditya Iryawan; Nuzlan Nuari; Betta Mega Oktaviana; Adrian Avicenna; Rosandhy Alifiyah Pramesti (UNUSA Press, 2025)
Air quality in Surabaya faces serious challenges due to motor vehicle emissions, industrial pollution, and a lack of green space, which directly impact public health, especially the respiratory system, leading to diseases such as asthma and bronchitis. To address this, a community service program using lecture and simulation methods was conducted, involving 40 male and female students at an Islamic boarding school. The lecture lasted 40 minutes, using PPT and poster media, and pre- and post-test questionnaires to measure participants knowledge improvement. Furthermore, a simulation was conducted in collaboration with the Islamic boarding school to plantbamboo palms on May 11, 2024. The results showed a significant increase in students knowledge about the benefits of bamboo palms as an effort to prevent air pollution, with a significant difference in pre- and post-test scores. The lecture approach accompanied by visual media proved effective in increasing understanding of the role of bamboo palms in reducing pollution in the Islamic boarding school environment, so this education successfully raised students awareness of the importance of air pollutioncontrol efforts.